Treatment of Osteochondrosis Dissecans of the Canine Stifle Using Synthetic Osteochondral Resurfacing - Egan, Pádraig; Murphy, Susan; Jovanovik, Jelena; Tucker, Russell; Fitzpatrick, Noel (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective This article aimed to describe the use and evolution of a synthetic osteochondral resurfacing (SOR) implant in the treatment of osteochondrosis dissecans (OCD) of the femoral condyle and to report the clinical, radiographic, computed tomography and magnetic resonance imaging outcomes of this technique.Methods Medical records of dogs that were treated with first-generation (G1) and second-generation (G2) SOR at a single institute were reviewed. Surgical reports and clinical examinations as well as the preoperative, postoperative, and follow-up radiographs, computed tomographic images and magnetic resonance imaging images were reviewed.Results Fourteen stifles (nine dogs) were included in the study. G1-SOR implants were employed in six stifles of four dogs and G2-SOR implants in eight stifles of five dogs. Osteochondrosis dissecans of the medial femoral condyle was confirmed as the sole pathology in all dogs treated with G1-SOR. Only one of eight OCD lesions was located on the medial condyle in the G2-SOR group with the remaining seven lesions affecting the lateral femoral condyle. At 12 weeks, 13 of 14 stifles displayed implant stability, with no subchondral bone changes or evidence of lucency around any implant. Eight of nine dogs achieved a good-excellent clinical outcome. Complications included one minor surgical site infection and one infective arthritis which required implant removal.Clinical Significance In this cohort of dogs, both G1-SOR and G2-SOR were successful and repeatable surgical procedures for dogs with OCD of the femoral condyle.
Keywords: osteochondral defects; osteochondrosis dissecans; stifle; osteochondral resurfacing